Regionalizing science : placing knowledges in Victorian England - Naylor, Simon (Science and culture in the nineteenth century ;, 2016)
Victorian England, as is well known, produced an enormous amount of scientific endeavour, but what has previously been overlooked is the important role of geography on these developments. This book seeks to rectify this imbalance by presenting a historical geography of regional science.